Relationship Between Results of Genexpert RT-PCR and Erythrocyte Sedimentation Rate in Suspected Tuberculosis Patients - Listiyowati, Tanti; Wardani, Dita Pratiwi Kusuma; Sudarsono, Tantri Analisawati; Wijayanti, Linda (Poltekkes Kemenkes Jakarta III, 2023)
Pulmonary tuberculosis (TB) is an infectious disease that attacks the lungs and is caused by the bacterium Mycobacterium tuberculosis. The GeneXpert RT-PCR examination (Xpert MTB / RIF) is a development of a diagnostic tool that can automatically detect the presence of Mycobacterium tuberculosis (MTB) by molecular examination and can be used to detect MTB resistance to rifampicin. Erythrocyte sedimentation rate (ESR) is a test used to determine the rate at which erythrocytes settle in the blood. The purpose of this study was to determine the relationship between GeneXpert RT-PCR results and ESR in suspected tuberculosis patients. This research uses a cross-sectional study. The sample used in this study were 56 new suspected TB patients who had never been treated for ATD and underwent GeneXpert RT-PCR examination. Sampling was carried out by purposive sampling with the TCM Rif Sen group and negative results. A total of 27 patients (96.4%) with Rif Sen's GeneXpert RT-PCR results had high ESR values. 15 patients (53.6%) with negative GeneXpert RT-PCR results had normal ESR values. The results of the Chi Square test (X2) show that p-value = 0.000 OR = 0.032. There is a significant relationship between GeneXpert and ESR values ​​in suspected tuberculosis